2022
DOI: 10.31258/sorot.17.3.167-176
|View full text |Cite
|
Sign up to set email alerts
|

The role of financial attitude, financial experience, financial knowledge and personality on student’s personal financial management behavior

Abstract: Penelitian ini bertujuan untuk mengidentifikasi peran dari sikap keuangan, pengalaman keuangan, pengetahuan keuangan dan kepribadian, terhadap perilaku pengelolaan keuangan pribadi mahasiswa. Populasi adalah seluruh mahasiswa asal Propinsi Sumatera Utara yang berkuliah di universitas negeri di Kota Langsa. Instrumen pengumpulan data nerupa kuesioner disebar melahui grup Whatsapp (WA) menggunakan google form, dan diperoleh 150 responden yang merespon. Berdasarkan hasil analisis regresi berganda, diperoleh secar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
2
2
1
Order By: Relevance
“…The results of this study are in line with research conducted by (Anggraini et al, 2022), (Asmin et al, 2021), ) (Thi et al, 2015), found that financial attitudes have a significant effect on personal financial behavior. However, this research is not in line with research conducted by (Sahara & Fuad, 2022) who found that only financial knowledge has a significant effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of this study are in line with research conducted by (Anggraini et al, 2022), (Asmin et al, 2021), ) (Thi et al, 2015), found that financial attitudes have a significant effect on personal financial behavior. However, this research is not in line with research conducted by (Sahara & Fuad, 2022) who found that only financial knowledge has a significant effect.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study are in line with the results of research conducted (Anisyah et al, 2021), (Harahap et al, 2020), (Sahara & Fuad, 2022) found that financial knowledge has a significant effect on personal financial management behavior.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Acquiring financial knowledge necessitates honing financial skills and mastering the utilization of financial tools. Sahara, Fuad, and Setianingsih (2022) and Wahyuniati, Ibnu, and Jumadania (2022) concur with the preceding study, asserting that financial knowledge encompasses comprehension of all financial aspects and tools, including their proficient utilization. The possession of financial information and skills empowers individuals to make informed investment decisions.…”
Section: Literature Reviewsupporting
confidence: 79%
“…Extrovertism hurt financial planning, whereas neuroticism and conscientiousness had a positive influence, according to a study by Ghaffar et al (2022). Lastly, Sahara et al (2022) discovered that financial attitudes and personality did not significantly affect personal financial management behavior, but financial experience and knowledge did. These findings imply that a variety of personality traits may have an impact on students' financial management practices.…”
Section: Introductionmentioning
confidence: 99%